Cankar’s novel Milan and Milena, the first fairy-tale novel in Slovenia - Zupan Sosič, Alojzija (Slavia Centralis, 2021)
Cankar’s tenth novel Milan and Milena (1913) is marked by genre, story and narrative innovations. It is not only the author’s first fairy-tale novel, but is also the first Slovenian fairy-tale novel, the fairy-tale of which is determined by symbolist aesthetics with poetic beauty and suggestive longing. Whereas the fairy-tale perspective sencompasses the idealisation of the fairy-tale as another (more beautiful and better) world, the fairy-tale framework consists of two qualities: the fairy-tale beginning and relocation. Beside genre innovations there are important story and narrative innovations: love as the supreme value and symbolist element, longing as a way out of modern nihilism, loneliness and boredom as a signifier of noble individualism, critique of capitalist society through the optics of masculinity and femininity, and the narrative parallelism or parallelism of the male and female perspective.
Keywords: contemporary artistic fairy-tale; symbolist aesthetics; fairy-tale perspective; genre, story and narrative innovations